2021
DOI: 10.3390/buildings11060231
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Occupants’ Satisfaction in Governmental Buildings: The Case of the Kingdom of Bahrain

Abstract: Satisfaction is a very important factor in improving productivity and performance in the work environment. This study aims to investigate the levels of occupants’ satisfaction with the indoor environmental quality (IEQ) in the governmental buildings in the Kingdom of Bahrain and to investigate the impact of occupants’ demographics and building attributes (non-IEQ factors) on these levels. For these purposes, the study used a questionnaire that has 17 indoor environmental quality (IEQ) factors in addition to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 122 publications
0
6
0
Order By: Relevance
“…Therefore, an increasing number of previous studies are analyzing the IEQ evaluation of residents through correlation with various factors. In previous studies, it was confirmed that the job type was also correlated with the IEQ evaluation of the occupant [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. However, because IEQ can obtain different research results depending on buildings and regions, research on various targets and factors should continue, and it is necessary to obtain additional relevant scenarios to analyze correlation data.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Therefore, an increasing number of previous studies are analyzing the IEQ evaluation of residents through correlation with various factors. In previous studies, it was confirmed that the job type was also correlated with the IEQ evaluation of the occupant [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. However, because IEQ can obtain different research results depending on buildings and regions, research on various targets and factors should continue, and it is necessary to obtain additional relevant scenarios to analyze correlation data.…”
Section: Introductionmentioning
confidence: 59%
“…Kamaruzzaman [ 37 ] analyzed the correlation between IEQ and the satisfaction of occupants of office buildings and found that the “managerial staff” had the highest average IEQ score among all occupational groups, which included the “clerical and secretarial”, “professional”, “managerial”, and “other” staff. Albuainain [ 38 ] investigated the level of IEQ satisfaction for government buildings in Bahrain and analyzed its correlations with non-IEQ factors, such as occupational groups. They found that the IEQ satisfaction level was different depending on the occupational group, and that the technical group had the highest IEQ satisfaction among the five occupational groups.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the number of paper questionnaires distributed to users (5% of authors) and the number of telephone interviews conducted (1%) in the studies evaluated in this review were marginal. The first tool, as described by the authors in [ 131 , 132 , 133 ], was applied to prefabricated timber houses in the UK, government buildings in the Kingdom of Bahrain, and universities in Cairo (Egypt), respectively. The second, on the other hand, was described by the authors in [ 134 ], in which it was used to understand how facilities’ managers reacted to user feedback and its impact on users’ post-feedback behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…They stated that this was achieved by optimizing the HVAC operation based on occupants' feedback. After reviewing similar studies (Albuainain et al, 2021;Zhang et al, 2018), the authors observed that occupants might be oblivious to maintenance issues in a facility. Besides, certain studies have investigated building performance evaluation and postoccupancy evaluation, which addressed HVAC systems in health-care facilities (Brambilla and Capolongo, 2019;Dilrukshi et al, 2014;Forouharmajd et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%